Insight into Two ABC Transporter Families Involved in Lantibiotic Resistance - Clemens, Rebecca; Zaschke-Kriesche, Julia; Khosa, Sakshi; Smits, Sander H. J. (Frontiers in Molecular Biosciences, 2018)
Antimicrobial peptides, which contain (methyl)-lanthionine-rings are called lantibiotics. They are produced by several Gram-positive bacteria and are mainly active against these bacteria. Although these are highly potent antimicrobials, some human pathogenic bacteria express specific ABC transporters that confer resistance and counteract their antimicrobial activity. Two distinct ABC transporter families are known to be involved in this process. These are the Cpr- and Bce-type ABC transporter families, named after their involvement in cationic peptide resistance in Clostridium difficile, and bacitracin efflux in Bacillus subtilis, respectively. Both resistance systems differentiate to each other in terms of the proteins involved. Here, we summarize the current knowledge and describe the divergence as well as the common features present in both the systems to confer lantibiotic resistance.